ANALISIS KELAYAKAN BISNIS KEDAI CANDU COFFEE DI KOTA PANGKALPINANG - Sariman; Manullang, Rizal Ruben; Maharani, Yunita (Jurnal Progresif Manajemen Bisnis, 2023)
Business is a series of economic activities that have an important role in meeting human needs. Business activities have an influence on the level of human life both individually and in social groups. Candu Coffee was established with the aim of providing service and convenience to consumers in enjoying free time and enjoying the dishes served by cafes by creating a more modern and aesthetically pleasing concept. This study aims to determine the business of the Pangkalpinang Opium Coffee shop. The author uses qualitative research methods, namely field research and library research, data collection methods by observation, interviews, and documentation sourced from primary data and secondary data. The conclusion from this study is that the cafe business at Candu Coffee is feasible to run by fulfilling the marketing mix requirements. The suggestion from this study is to reduce unfavorable comments from consumers, especially on portions and taste. In order for the cafe to get enough profit, the owner can increase the price a little more to increase revenue and cash calculations so that it is not too low and in accordance with the standard pricing. In order to attract the attention of visitors, the owner must be more critical in choosing and adding places or locations. The cafe should add facilities such as tables and chairs, lights that are bright enough to add to the aesthetics and beauty of the room.